Cardiodynamic variables measured by impedance cardiography during a 6-minute walk test are reliable predictors of peak oxygen consumption in young healthy adults. - Fang Liu (Public Library of Science (PLoS), 2021)
Accurate prediction of aerobic capacity is necessary to guide appropriate exercise prescription. It is common to use 6-minute walk distance (6MWD) to predict peak oxygen uptake (VO2peak) in the clinical environment. The aim of this study was to determine whether prediction of VO2peak can be improved by the inclusion of cardiovascular indices derived by impedance cardiography (ICG) during the 6MWT. A total of 62 healthy university students aged 21±1 years completed in separate days, a cardiopulmonary exercise test (CPET) and two 6MWTs (30 min apart), during which heart rate (HR), stroke volume (SV) and cardiac output (CO) were measured by ICG (PhysioFlow® PF07 EnduroTM). The CPET was conducted with the Ergoselect 200 Ergoline and oxygen consumption measured by a MasterScreenTM CPX breath-by-breath metabolic cart. Multiple regression analyses were conducted to generate VO2peak prediction equations using 6MWD with, or without the cardiovascular indices recorded at the end of the best performed 6MWT as predictor variables. The mean peak HR (bpm), SV (ml) and CO (L/min) recorded during 6MWT were 156±18, 95.6±9, 15±2.8 and during CPET were 176±16, 91.3±8, 16.2±2.7, respectively. Analyses revealed the following VO2peak prediction equation: VO2peak = 100.297+(0.019x6MWD)+(-0.598xHR6MWT)+(-1.236xSV6MWT) + (8.671 x CO6MWT). This equation has a squared multiple correlation (R2) of 0.866, standard error of the estimate (SEE) of 2.28 mL/kg/min and SEE:VO2peak (SEE%) of 7.2%. Cross-validation of equation stability using predicted residual sum of squares (PRESS) statistics showed a R2 (Rp2), SEE (SEEp) and SEEp% of 0.842, 2.38 mL/kg/min and 7.6% respectively. The minimal shrinkage of R2 implied regression model stability. Correlation between measured and predicted VO2peak using this equation was strong (r = 0.931, p<0.001). When 6MWD alone was used as the predictor for VO2peak, the generated equation had a lower R2 (0.549), and a higher SEE (4.08 mL/kg/min) and SEE% (12.9%). This is the first study which included cardiac indices during a 6MWT as variables for VO2peak prediction. Our results suggest that inclusion of cardiac indices measured during the 6MWT more accurately predicts VO2peak than using 6MWD data alone.